0008 SUVN-G3031, A Histamine H3 Receptor Inverse Agonist Produces Robust Wake Promoting and Anticataplectic Activity in Orexin Knockout Mice. (27th May 2020) - Benade, V; Daripelli, S; Petlu, S; Subramanian, R; Bhyrapuneni, G; Shinde, A; Rasheed, M; Jayarajan, P; Choudakari, P; Nirogi, R
Abstract: Introduction: Narcolepsy is a sleep disorder characterized by excessive daytime sleepiness, sleep paralysis, hallucinations, and in some cases episodes of cataplexy. Results from animal studies indicate the involvement of deficient orexin transmission in narcolepsy which can be circumvented by the activation of histaminergic neurons. SUVN-G3031 is a potent and selective histamine H3 receptor inverse agonist with hKi of 8.7 nM and shows less than 50% inhibition at 1 µM against 70 other targets. SUVN-G3031 exhibited excellent pharmacokinetic properties and brain penetration in preclinical species. Oral administration of SUVN-G3031 produces significant increase in histamine, dopamine and norepinephrine levels in the rat cortex. Long-term safety studies in animals have been successfully completed without any concern for further development of SUVN-G3031. In the present study, the effects of SUVN-G3031 were evaluated in orexin knockout mice, a reliable animal model of narcolepsy as a proof-of-concept study for the treatment of narcolepsy with and without cataplexy. Methods: Male orexin knockout mice (10 - 15 weeks old, 25 - 35 g at the time of surgery) were implanted with telemetric device for simultaneous monitoring of electroencephalography (EEG) and electromyography. Animals were allowed surgical recovery of 3 weeks prior to EEG recording. Effects of SUVN-G3031 (3 and 10 mg/kg, p.o .) were evaluated during active period of animals. Results: SUVN-G3031 produced significant increase in wakefulness with concomitant decrease in non-rapid eye movement sleep in orexin knockout mice. SUVN-G3031 also significantly decreased the number of cataplectic episodes in orexin knockout mice. Conclusion: Results from the current preclinical study provide a strong basis for the utility of SUVN-G3031 for the treatment of narcolepsy with and without cataplexy. SUVN-G3031 is currently being evaluated in a Phase 2 study as monotherapy for the treatment of narcolepsy with and without cataplexy (ClinicalTrials.gov Identifier: NCT04072380). Support: None